Science and Fiqh in 10th Century AH: Examining Ibn Hajar al-Haytami's Views on Ru'yah al-Hilāl - Munif, Ahmad; Wildan, David; Qulub, Siti Tatmainul (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
Ibn Hajar al-Haytami (d. 974 AH/1567 CE) gave his own color and demonstrated the development of ru'yah al-hilāl in Islamic civilization. As an important part of determining the beginning of Ramadan for the obligation to fast, Ibn Hajar al-Haytami was of the view that the results of ru'yah al-hilāl that utilized tools such as glass could not be accepted or used as guidelines for determining the beginning of the lunar month. This view contradicts the work of science that prioritizes and produces observation aids to maintain precision and reduce human error when observing celestial objects. With a historical and hermeneutic approach, this paper seeks to reveal the historical background of Ibn Hajar al-Haytami 's view regarding ru'yah al-hilāl. The findings of this paper are that Ibn Hajar al-Haytami's opinion is in line with and influenced by the decline of scientific civilization in Islam in the 10th century AH. At that time, especially in the Ottoman Turkish region, philosophy as the basis for the development of science was rejected and/or ignored in the scientific treasures of Islamic civilization.